Dakwah Influencer: Analisis Konten Dakwah Neng Umi Laila di Media Sosial - Reny Masyitoh; Moch Nurcholis Majid (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2024)
This article discusses how millennial da'wah activities utilize technology, the language and rhetoric of da'wah, but can also be a resource for the young generation of Muslims who are educated in preaching in the digital era. Meanwhile, to explain the da'wah on social media that is used in da'wah when Neng Umi Laila gives it, as well as the difficulties and possibilities that Neng Umi Laila faces in advancing da'wah in the era of digital technology, with the method. The research method used in this research is qualitative with a library approach , the data sources are Ning Umi Laila's social media and scientific articles to support this research. And it results in a conclusion that Ning Umi Laila is a young influencer preaching who is very popular with the public. Apart from that, Ning Umi Laila also actively uses social media as a medium to support da'wah in the digital era. By utilizing this digital media, Ning Umi Laila can be categorized as a da'wah influencer who has her own charisma, both in terms of a beautiful face, a polite but elegant dressing style, politeness in delivering her da'wah and being humorous in each of her da'wah and active in producing da'wah and prayer content in the media. social media are Instagram, TikTok and YouTube.